‘We Got Our Quota’: Black Female Educators and Resistive Pedagogies, 1960s-1980s - Aladejebi, Funke (Ontario History)

(untitled) (The Ontario Historical Society, 2015)
Examining the oral histories of black women teachers, this article explores the ways in which black women’s workplace experiences in Ontario schools and, to a larger extent, broader Canadian society, influenced the development of their educational philosophies. Offering a critical lens towards Ontario’s education system, black female educators not only developed resistive pedagogies to cope with the isolation and discrimination they experienced as teachers, but also created strategies that allowed them to educate the children they were responsible to teach. These resistive pedagogies recognized and supported black experiences in Canada and were firmly rooted in their experiences as black women. By teaching black history within their classrooms, merging community uplift with schooling practice, and implementing strict guidelines and expectations for racialized students, black women worked to augment mainstream schooling practices to better serve students of various racial and cultural backgrounds.